Small artificial waterbodies are widespread and persistent emitters of methane and carbon dioxide. (10th July 2021) - Peacock, M.; Audet, J.; Bastviken, D.; Cook, S.; Evans, C. D.; Grinham, A.; Holgerson, M. A.; Högbom, L.; Pickard, A. E.; Zieliński, P.; Futter, M. N.
Abstract: Inland waters play an active role in the global carbon cycle and emit large volumes of the greenhouse gases (GHGs), methane (CH4 ) and carbon dioxide (CO2 ). A considerable body of research has improved emissions estimates from lakes, reservoirs and rivers but recent attention has been drawn to the importance of small, artificial waterbodies as poorly quantified but potentially important emission hotspots. Of particular interest are emissions from drainage ditches and constructed ponds. These waterbody types are prevalent in many landscapes and their cumulative surface areas can be substantial. Furthermore, GHG emissions from constructed waterbodies are anthropogenic in origin and form part of national emissions reporting, whereas emissions from natural waterbodies do not (according to Intergovernmental Panel on Climate Change guidelines). Here, we present GHG data from two complementary studies covering a range of land uses. In the first, we measured emissions from nine ponds and seven ditches over a full year. Annual emissions varied considerably: 0.1–44.3 g CH4 m −2 year −1 and −36–4421 g CO2 m −2 year −1 . In the second, we measured GHG concentrations in 96 ponds and 64 ditches across seven countries, covering subtropical, temperate and sub‐arctic biomes. When CH4 emissions were converted to CO2 equivalents, 93% of waterbodies were GHG sources. In both studies, GHGs were positively related to nutrient status (C, N, P), and pond GHG concentrations were highest in smallest waterbodies. Ditch and pond emissions were larger per unit area when compared to equivalent natural systems (streams, natural ponds). We show that GHG emissions from natural systems should not be used as proxies for those from artificial waterbodies, and that artificial waterbodies have the potential to make a substantial but largely unquantified contribution to emissions from the Agriculture, Forestry and Other Land Use sector, and the global carbon cycle. Abstract : Drainage ditches and constructed ponds are common features of many landscapes. Here, we show that these waterbodies emit large amounts of the greenhouse gases methane and carbon dioxide to the atmosphere, and thus contribute to climatic warming. Although small, these waterbodies can occupy cumulatively large areas, and have the potential to influence landscape‐scale greenhouse gas budgets. Because these waterbodies are constructed (non‐natural), these emissions must count as being the result of human activity, and therefore must be included in national inventories of greenhouse gases.